Analisis Joint Balok Kolom dengan Metode SNI 2847-2013 dan ACI 352R-2002 pada Hotel Serela Lampung - Ristanto, Eddy; Suyadi, Suyadi; Irianti, Laksmi (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2015)
This study aimed to analyze the relationship beam-column design at Building Serela LampungHotel, which refers to SNI 2847-2013 and Methods ACI 352R-2002. In the analysis, the existingshear force on beam-column joint relationship is greater than the shear forces that are on thebeams and columns. Therefore it is necessary that the relationship between the shearreinforcement. From a review of existing columns and beam size is sufficient to carry the shearforces that occur. There are differences between the results of the review of planning method SNI2847-2013 and methods ACI 352R-2002. From the results obtained with SNI 2847-2013 shearforce to review the interior, roof interior, exterior, roof exterior, corner, and roof cornersequentially as follows: 1682.544 KN; 1380.365 KN; 607.759 KN; 364.932 KN; 607.759 KN;364.932 KN. While the method of ACI 352R-2002 as follows: 1712.750 KN; 1440.799 KN;632.642 KN; 413.498 KN; 632.642 KN; 413.498 KN. Although both methods are considered safein the planning of the object of study Serela Lampung Hotel but in general planning methods ACI352R-2002 a higher level of safety and efficiency in terms of planning method SNI 2847-2013 evengreater levels of efficiency.Keywords: SNI 2847-2013, ACI 352R-2002, joint, beams, columns, seismic load, shear force,inelastic.